Penilaian Dan Evaluasi Dalam Pendidikan IPS - Aliif Adrian Mamahit; Anjani Rizki Pauzia; Hamdan Septihadi; Neng Eva Nafisah; Selawati Nur Oktapiani; Tita Zikrilla Utami; Budi Azhari (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Man is a creature given reason by God who works to distinguish between the right and the wrong. The ability of the mind is strongly influenced by the knowledge and experience experienced by each individual. In order to maximize these abilities, human beings must obtain quality education. A quality education can be obtained if the teaching process is done well. In this process, to be able to know whether the educational process is going well or not it can be seen from the assessment and evaluation stages. So from that, this article was compiled to give a brief overview of assessment and evaluation in social science education.